2020
DOI: 10.1002/cncr.32912
|View full text |Cite
|
Sign up to set email alerts
|

Impact of pathologic lymph node‐positive renal cell carcinoma on survival in patients without metastasis: Evidence in support of expanding the definition of stage IV kidney cancer

Abstract: Background Stage III renal cell carcinoma (RCC) encompasses both lymph node‐positive (pT1‐3N1M0) and lymph node–negative (pT3N0M0) disease. However, prior institutional studies have indicated that among patients with stage III disease, those with lymph node disease have worse oncologic outcomes and experience survival that is similar to that of patients with American Joint Committee on Cancer (AJCC) stage IV disease. The objective of the current study was to validate these findings using a large, nationally re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 22 publications
0
22
0
Order By: Relevance
“…The NCDB, a national oncology registry, records approximately 70% of the incident cancer cases in the United States. It contains information regarding patient demographics, neoplasm staging (both clinical and pathologic staging), surgical treatment, and survival outcomes [12] , [13] , [14] .…”
Section: Methodsmentioning
confidence: 99%
“…The NCDB, a national oncology registry, records approximately 70% of the incident cancer cases in the United States. It contains information regarding patient demographics, neoplasm staging (both clinical and pathologic staging), surgical treatment, and survival outcomes [12] , [13] , [14] .…”
Section: Methodsmentioning
confidence: 99%
“…However, the risk of progression is distinctly different for LA/M0 and LN+/M0 tumors, and this should be considered in trial analyses. Using population‐level data, Srivastava et al 7 provide compelling evidence and validate institutional studies demonstrating the different clinical phenotypes for LA/M0 tumors versus LN+/M0 tumors. It is critical that future editions of the American Joint Committee on Cancer staging system recognize the increased risk with LN+/M0 tumors and consider reclassification of LN+/M0 tumors as stage IV tumors so that baseline risks are more accurately measured in these rare populations.…”
mentioning
confidence: 71%
“…However, the results of this study are difficult to interpret because only 4% of the patients had lymph node metastases. Although slightly less than one‐third of patients in EORTC 30881 had ≥pT 3 tumors, the incidence of positive lymph nodes was more than 10‐fold less than that for pT 3 tumors in the study by Srivastava et al 7 The current guidelines recommend that surgeons may remove radiographically or grossly involved retroperitoneal lymph nodes, primarily for staging purposes, 10,11 but there is no consensus on LND for RCC with lymph nodes that are not enlarged. Blute et al 12 identified sarcomatoid dedifferentiation, a primary tumor size >10 cm, pT 3 to pT 4 tumors, tumor necrosis, and tumor grade 3 to 4 to be associated with pathologic nodal involvement.…”
mentioning
confidence: 92%
See 2 more Smart Citations